Volatility transmission and asymmetric effect between stock and foreign exchange markets among the brics - Khoo, Wai Hoe (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study examines the pattern of volatility transmission and asymmetric effects between the stock and foreign exchange market among the BRICs (Brazil, Russia, India and China) after the recognition on BRICs concept in 2003. By using weekly data across the study period 1st January 2003 until 31st December 2010, the results reveal that the incongruities of the volatility transmission structure exist among the BRICs. The evidence was also found that the BRICs markets’ volatility was driven by the negative innovations (bad news). Generally, the investment portfolio diversification and hedging strategy within the stock and foreign exchange market in BRICs shall be considered.